MEDICATION ADHERENCE IN POST MYOCARDIAL INFARCTION PATIENTS - Hussain, Saba; Jamal, Syed Zahid; Qadir, Faisal (Journal of Ayub Medical College Abbottabad, 2018)
Background: Medication non-adherence after acute myocardial infarction is a global problem causing increased morbidity and mortality. This multifaceted problem has not been well studied in our part of the world. Our study aimed to determine the burden of medication non-adherence in post myocardial infarction patients. Methods: This cross-sectional study was conducted at National Institute of Cardiovascular disease, Karachi, from December 2016 to June 2017. A total of 350 patients were included at the time of discharge after their first myocardial infarction (MI) of which follow up was completed for 315 patients. Baseline characteristics and discharged drug data were collected for each individual. Patients were called at 7th day, 1 and 3months post discharge and were assessed for the medication adherence using Morisky medication adherence scale. They were stratified accordingly into self-reported high, moderate and low groups. Chi- square test was used to determine significant relationship between variables. The level of significance was set at level of p value ‰¤0.05. Results: Among 315 patients, only 45% patients were adherent to prescribed drugs at 7th day follow up and the adherence further reduces to 19% at 3rd post MI month (p-value <0.001). High income, male gender, and presence of partner persistently showed significantly higher medication adherence. Factors like younger age, addiction and advance education showed higher adherence only in early follow up periods. However, presence of comorbidities, intervention and specific diagnosis had no significant impact. The most common stated reasons for non-adherence were forgetfulness and poor understanding of drugs. Conclusion: Adherence to prescribed medication in post myocardial infarction patients was found to be strikingly suboptimal, contributed by multiple factors. Modification of these factors would likely improve patient adherence to medication and eventually long-term outcome. Keywords: Acute myocardial infarction; Medication adherence